The use of Kohonen`s neural networks in the recruitment process for sport swimming - Roczniok, R.; Rygula, I.; Kwasniewska, A. (Journal of Human Kinetics, 2006)
Being a long-term and complex process, contemporary sport training requires continuous inflow of information conditioning its effectiveness. This information is used in training control, understood as the issue of decisions based on information concerning the condition of the control process and knowledge of control objective (Raczek 1989). There are many factors influencing the effectiveness of the training process, and the sport selection process is one of them. Its essence consists in determining the talent vector of the candidate for sport training, which allows for increasing the effectiveness of sport training (Rygula 2002).